SEMINAL PLASMA REMOVAL IMPROVES CRYOPRESERVED SEMEN QUALITY IN GADDI BUCKS - SHARMA, A; SOOD, P; DOGRA, PK (The Indian Journal of Animal Reproduction, 2022)
Forty-eight semen ejaculates, collected in artificial vagina, from eight adult Gaddi bucks were randomly divided into groups viz. freezing the entire semen sample (n=24) or removal of seminal plasma by centrifugation (n=24). Semen was extended in tris citrate egg yolk extender to maintain 150 million sperm / dose (0.25 ml). The filling, sealing, equilibration, vapour freezing and final plunging in liquid nitrogen was done as per the standard norms. The post-thaw results (%) of washed semen samples were better (p<0.05) than their non-washed counterparts (progressive motility 30.4±1.6 vs. 22.8±2.1; morphological abnormalities 9.7±0.9 vs. 14.3±0.8; HOST 61.5±2.0 vs. 45.6 ±3.8). In conclusion, the removal of seminal plasma in cryopreservation protocol of Gaddi buck semen appears essential to obtain better post-thaw results.